2016
DOI: 10.1155/2016/3029810
|View full text |Cite|
|
Sign up to set email alerts
|

Glutathione Peroxidase Level in Patients with Vitiligo: A Meta-Analysis

Abstract: Abnormality of glutathione peroxidase (GPx) is involved in the etiology and pathogenesis of vitiligo. However, the results were controversial. Aim. The purpose of this meta-analysis is to compare the levels of GPx between vitiligo patients and healthy controls. Methods. Relevant published articles were searched according to eligibility criteria. A meta-analysis was conducted to pool estimates of the standardized mean difference (SMD) with 95% confidence interval (CI). Results. Twenty-three studies with a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
(13 reference statements)
2
20
1
1
Order By: Relevance
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px . Our study showed that EGb761 could significantly restore the activity of SOD and GSH‐Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px . Our study showed that EGb761 could significantly restore the activity of SOD and GSH‐Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionsupporting
confidence: 93%
“…10 The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH-Px. 20,21 Our study showed that EGb761 could significantly restore the activity of SOD and GSH-Px in PIG1 cells under H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…It showed a significant relationship between low GPx level and vitiligo. Asian vitiligo patients showed lower levels of GPx than the controls, Caucasian populations, and healthy controls [81]. GPx polymorphism may contribute to the reduced GPx activity and the prevalence of vitiligo in Gujarat population [82].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…The expression level and activity of GPx are decreased in blood and skin of vitiligo patients (Xiao et al, 2016), and the genetic association of vitiligo with variations in GPx gene was confirmed by Mansuri et al (2017). Thioredoxin reductase (TxR) reduces the LMWA thioredoxin repristinating its ROS scavenging activity.…”
Section: Theories About Melanocytes Destruction and Oxidative Stresmentioning
confidence: 97%